2021
DOI: 10.24191/jsst.v1i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Way Forward for Implementing Green Roof in Construction Industry in Sarawak, Malaysia

Abstract: There is a growing global concern about the adverse effects of today's rapid economic growth and development, which impact the environment and deplete energy supply. A green roof may lower a building's energy consumption and minimise air pollution by reducing dust particles in the air. The primary impediment to green roof implementation in Malaysia lacks local knowledge and unskilled green roof specialists. As a result, there is a shortage of green roof installers and specialised firms in the country. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, there is no report found that Malaysia implemented this subsidy scheme. Abdul Rahim [67] also reports that the lack of subsidies in Malaysia is one of the obstacles to enormous propagation of GRs in society. The study concludes that government has a significant impact on the development of green roofs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no report found that Malaysia implemented this subsidy scheme. Abdul Rahim [67] also reports that the lack of subsidies in Malaysia is one of the obstacles to enormous propagation of GRs in society. The study concludes that government has a significant impact on the development of green roofs.…”
mentioning
confidence: 99%
“…According to the findings of Shams, survey research on user perception in Brunei resulted less interest in GRs [48]. Several studies in Malaysia indicated that the lack of GR expertise in the country remained a significant issue [67,102]. Arif [103] described that a method for enhancing public interest in green roofs can be initiated by introducing GRs to the community in public places.…”
mentioning
confidence: 99%